2020
DOI: 10.1017/s0007114520002342
|View full text |Cite
|
Sign up to set email alerts
|

A New Zealand green-lipped mussel oil-enriched high-fat diet exhibits beneficial effects on body weight and metabolism in mice

Abstract: To induce diet-induced obesity (DIO) in rodents, diets high in saturated fat and/or carbohydrates are commonly used. In the laboratory, standardized diets evolved over time without having paid particular attention to the effect of fat composition on metabolic alterations. In the present study, customized high-fat diets (HFDs) enriched in a combination of lard and different concentrations of New Zealand green-lipped mussel (Perna canaliculus) oil or Hoki (Macruronus novaezelandiae, blue grenadier) liver oil, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…The data showed decreased lipid profiles among all groups, especially the group with the highest mussels in its diet. The data are consistent with the literature, where a P. canaliculus diet affects visceral fat in rodents (Loehfelm et al., 2020). In addition, the LDL‐C level was significantly reduced in the group with the highest level of P. canaliculus in the diet, thus indicating a reduction in the inflammatory response in several chronic and acute inflammatory disorders such as atherosclerosis, as shown in previous studies (Cetin et al., 2020; Singh et al., 2008; Siriarchavatana et al., 2020; Whitehouse et al., 1997).…”
Section: Discussionsupporting
confidence: 93%
“…The data showed decreased lipid profiles among all groups, especially the group with the highest mussels in its diet. The data are consistent with the literature, where a P. canaliculus diet affects visceral fat in rodents (Loehfelm et al., 2020). In addition, the LDL‐C level was significantly reduced in the group with the highest level of P. canaliculus in the diet, thus indicating a reduction in the inflammatory response in several chronic and acute inflammatory disorders such as atherosclerosis, as shown in previous studies (Cetin et al., 2020; Singh et al., 2008; Siriarchavatana et al., 2020; Whitehouse et al., 1997).…”
Section: Discussionsupporting
confidence: 93%
“…Fish, fish oil, and n-3 FA supplements, have been extensively studied as nutritional interventions to protect against metabolic diseases (19,(48)(49)(50) . In rodents, research suggests that supplementation of marine oils rich in long-chain n-3 FAs to a highfat diet (45-60% of total energy) can protect against cardiometabolic risk factors (51)(52)(53) . Loehfelm et al (53) showed that a high-fat (60% of total energy) diet enriched with mussel oil prevented dietinduced weight gain in young (~10-12 weeks of age) after 1 week of feeding, and either attenuated weight-gain or decreased weight in lean or obese, respectively, aged mice (~12 months of age) after four weeks of feeding.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, research suggests that supplementation of marine oils rich in long-chain n-3 FAs to a highfat diet (45-60% of total energy) can protect against cardiometabolic risk factors (51)(52)(53) . Loehfelm et al (53) showed that a high-fat (60% of total energy) diet enriched with mussel oil prevented dietinduced weight gain in young (~10-12 weeks of age) after 1 week of feeding, and either attenuated weight-gain or decreased weight in lean or obese, respectively, aged mice (~12 months of age) after four weeks of feeding. However, observational studies in humans assessing the effect of fish oil consumption on T2D risk are highly controversial (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, studying body composition in an intervention targeting obese women allows for the identification of a novel clinical marker, given the implication of sarcopenic obesity in the development of bone and joint disease. Recently, the novel weight-reducing potential of a GSM extract has been suggested from animal models (20,21) . Supplementation with a high-fat diet (HFD) enriched with GSM oil prevented body weight gain and was associated with decreased visceral fat mass in mice (20) .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the novel weight-reducing potential of a GSM extract has been suggested from animal models (20,21) . Supplementation with a high-fat diet (HFD) enriched with GSM oil prevented body weight gain and was associated with decreased visceral fat mass in mice (20) . In a previous study of rats fed with the HFHS diet, the inclusion of GSM powder tended to increase the lean mass gain and decreased the fat mass gain in comparison to rats fed with only HFHS (21) .…”
Section: Introductionmentioning
confidence: 99%